Sistem Pendukung Keputusan Kelayakan Penerima Subsidi Kepemilikan Rumah Menggunakan Adaptive Neuro-fuzzy Inference System - Barda Hudaya (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
The development of the world of Information Technology is so fast that the technology that has just become a trend has become obsolete in a short time. so that the existence of accurate, fast and reliable information is needed in various aspects of life. Armed with the problems arising from previous research, that is the result of not implementing government regulations properly so that the ownership of RSH is not exactly the target for this research is carried out so that the developer can make decisions to determine the feasibility of recipients of House ownership ready, decent or inappropriate which is required by grant recipients from low-income communities. As well as with the criteria used to help the developer or developer determine the feasibility of the recipient of the Ready to Own House (RSH) subsidy by applying the ANFIS method in developing its decision support system.